Metaphors of adult educators’ identity and practice - Tara Fenwick; Jim Parsons (Adult Education Research Conference, 1996)
Time is but a stream I go a-fishing-in. I drink at it; but while I drink I see the sandy bottom and detect how shallow it is. Its thin current slides away, but eternity remains. I would drink deeper; fish in the sky, whose bottom is pebbly with stars.—Thoreau Perhaps Thoreau’s words can help us reflect on the process of "making metaphors", an act of naming images that can help us consider the almost inexpressible parts of our existence. Once conjured into existence, a metaphor is like a pool of water. It can be revisited to sip or drink deeply from. Our study explores the metaphors adult educators use to describe their practice. We believe the exercise of creating metaphors helps educators become more self-aware and self-reflective. We have based our work on Deshler’s (1990) process of helping people create and examine personal metaphors as a method of fostering critical reflection.